Selective Sparing of Human Tregs by Pharmacologic Inhibitors of the Phosphatidylinositol 3‐Kinase and MEK Pathways. Issue 9 (23rd May 2016) - Zwang, N. A.; Zhang, R.; Germana, S.; Fan, M. Y.; Hastings, W. D.; Cao, A.; Turka, L. A.
Abstract : Phosphatidylinositol 3‐kinase (PI3K) and mitogen‐activated protein kinase/extracellular signal‐regulated (MEK) signaling are central to the survival and proliferation of many cell types. Multiple lines of investigation in murine models have shown that control of the PI3K pathway is particularly important for regulatory T cell (Treg) stability and function. PI3K and MEK inhibitors are being introduced into the clinic, and we hypothesized that pharmacologic inhibition of PI3K, and possibly MEK, in mixed cultures of human mononuclear cells would preferentially affect CD4 + and CD8 + lymphocytes compared with Tregs. We tested this hypothesis using four readouts: proliferation, activation, functional suppression, and signaling. Results showed that Tregs were less susceptible to inhibition by both δ and α isoform–specific PI3K inhibitors and by an MEK inhibitor compared with their conventional CD4 + and CD8 + counterparts. These studies suggest less functional reliance on PI3K and MEK signaling in Tregs compared with conventional CD4 + and CD8 + lymphocytes. Therefore, the PI3K and MEK pathways are attractive pharmacologic targets for transplantation and treatment of autoimmunity. Abstract : In vitro agents that block the PI‐3 kinase and/or MEK pathways preferentially block nonregulatory T cells, relatively sparing regulatory T cells, suggesting that these pathways may be attractive targets in transplantation.